Geothermal-solar hybrid power with the double-pressure evaporation arrangement and the system off-design evaluation. (15th September 2021) - Gong, Liang; Zhang, Yifan; Bai, Zhang
Highlights: A new geothermal-solar hybrid power generation system is proposed. The double-pressure evaporation configuration-based hybrid system is evaluated. The on-design and off-design properties of the system are numerically investigated. Concentrated solar energy offers a promising resource for geothermal hybrid utilization. Abstract: Geothermal-solar hybrid power generation is one of promising utilization technology of renewable energy, for effectively eliminating the inherent natures of solar intermittent and improving the low-temperature geothermal conversion efficiency. In this work, a novel hybrid power system with a double-pressure evaporation configuration is developed, the geothermal energy can be fully utilized to produce steams by providing considerable steam latent heat. The proportion of the input solar and geothermal energy can be readily coordinated, and the system thermo-economic analysis is then carried out under both the on-design and off-design conditions. A hybrid power system with the capacity of 10 MWe is designed in this work, the thermal efficiency and the geothermal share reach to 15.05% and 78.62%, respectively. By considering the off-design system modeling, the results indicate that the system annual energy efficiency could be improved to 12.19% with a 4-hour thermal storage, apart from enhancing the system flexible operation, the solar investment will significantly be reduced by enlarging the geothermal share, and then contributes to achieving a favorable solar based LCOE of 6.38 cents/kWh with a remarkable hybrid benefit. The research findings lay a favorable feasible foundation for renewable exploitation and CO2 emission reduction.